Happiness, habits and high rank: Comparisons in economic and social life - Andrew E. Clark (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The role of money in producing sustained subjective well-being seems to be seriously compromised by social comparisons and habituation. But does that necessarily mean that we would be better off doing something else instead? This paper suggests that the phenomena of comparison and habituation are actually found in a considerable variety of economic and social activities, rendering conclusions regarding well-being policy less straightforward.
Keywords: D01; D31; H00; I31; J12; J28; 330; comparison; habituation; income; unemployment; marriage; divorce; health; religion; policy